Effects of a News Literacy Video on News Literacy Perceptions and Misinformation Evaluation - Rita Tang; Melissa Tully; Leticia Bode; Emily K. Vraga (Media and Communication)
The mixing of misinformation with high-quality news and information on social media has reinvigorated interest in the value of news literacy (NL) to build audience resiliency to misinformation. Optimizing NL messages for social media environments—where they may be seen alongside misinformation—allows these messages to reach audiences when they are most likely to benefit from them. Using a 2 (NL video vs. control video) x 2 (sunscreen promotion video vs. sunscreen misinformation video) online survey experiment (N = 780), we examine whether exposure to an NL video improves perceived personal NL skills and value for news literacy, as well as enables participants to recognize and avoid engaging with misinformation. Our findings suggest that after watching the NL video, individuals valued NL more but their self-perceived news literacy did not improve. Furthermore, watching the NL video made individuals rate the second video as less credible and reduced engagement with it no matter whether the second video contained misinformation or quality information. This research has several important implications. While watching an NL video could protect individuals by discrediting and decreasing engagement with misinformation, it may do so at the expense of high-quality information. We discuss the difficulty in designing NL messages that lead people to be appropriately skeptical and able to discern between high- and low-quality health information, rather than cynically disengaging with media content altogether.